Oligomerization and tyrosine nitration enhance the allergenic potential of the birch and grass pollen allergens Bet v 1 and Phl p 5 - Fröhlich-Nowoisky, Janine; Bothen, Nadine; Backes, Anna T.; Weller, Michael G.; Pöschl, Ulrich (Frontiers in Allergy, 2023)
Protein modifications such as oligomerization and tyrosine nitration alter the immune response to allergens and may contribute to the increasing prevalence of allergic diseases. In this mini-review, we summarize and discuss relevant findings for the major birch and grass pollen allergens Bet v 1 and Phl p 5 modified with tetranitromethane (TNM, laboratory studies), peroxynitrite (physiological processes), and ozone and nitrogen dioxide (environmental conditions). We focus on tyrosine nitration and the formation of protein dimers and higher oligomers via dityrosine cross-linking and the immunological effects studied.